Vedolizumab: early experience and medium-term outcomes from two UK tertiary IBD centres. Issue 3 (10th August 2016) - Samaan, Mark A; Pavlidis, Polychronis; Johnston, Emma; Warner, Ben; Digby-Bell, Jonathan; Koumoutsos, Ioannis; Fong, Steven; Goldberg, Rimma; Patel, Kamal; Gulati, Shraddha; Medcalf, Lucy; Sastrillo, Marlene; et al.
Abstract : Objective: To gain an understanding of the efficacy of vedolizumab in a 'real-world' setting. Design: Retrospective cohort study using prospectively maintained clinical records. Setting: Two UK tertiary inflammatory bowel disease (IBD) centres. Patients: Patients with IBD commenced on vedolizumab at Guy's & St Thomas' and King's College Hospitals during November 2014–November 2015. Intervention: Vedolizumab, a monoclonal antibody to α-4 β-7 integrins that selectively inhibit leucocyte migration into the gut. Main outcome measures: Clinical disease activity was assessed at baseline, weeks 14 and 30 using Harvey–Bradshaw Index (HBI) for Crohn's disease (CD) and Simple Clinical Colitis Activity Index (SCCAI) for ulcerative colitis (UC). Response was defined as HBI or SCCAI reduction ≥3. Remission was defined as HBI <5 or SCCAI <3. Continuous data are summarised as medians, followed by range. Results: Fifty patients were included: 27 CD, 20 UC and 3 IBD-U (included in the UC group for analysis). At baseline visit, the median HBI was 8 (1–16) and SCCAI was 6 (0–15). At week 14, these values had fallen to 5 (0–15) (p=0.117) and 4 (0–10) (p=0.005), respectively. Additionally, week 30 data were available for 19 patients (9 CD, 10 UC). The clinical disease activity scores at that point were HBI 2 (0–7) (p=0.039) and SCCAI 2 (0–10) (p=0.023). At baseline, 37 (74%) of the 50 patients had clinically active disease. Of the patients with active disease, 22 (59%) responded and 14 (38%) achieved remission at week 14. Conclusions: Our early experience with vedolizumab demonstrates a clear benefit in terms of disease control as well as a steroid-sparing effect in a cohort, which included patients with complex and previously refractory disease.